Impact of Audit Committee Expertise on Earnings Management and External Auditor Moderation - Devira Yolla Aulia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Audit committees and external audits have a very important role for financial reporting and the tendency of corporate managers to manipulate earnings. Frequency is a key factor in reducing conflicts of interest and opportunistic behavior from managers. This study aims to examine the effect of the audit committee's financial expertise on earnings management with external auditors as moderation. In this study, there were 1,966 company data listed on the Indonesia Stock Exchange in 2016-2019. Earnings management variables, audit committee financial expertise, and external audit were analyzed using multiple linear regression models. The results showed that the financial expertise of the audit committee had a significant positive effect on earnings management. Audit committee expertise moderated by external audit has a negative and significant effect on earnings management.